Management of COVID-19 from the pulmonologist's perspective: a narrative review. (3rd April 2021) - Kumar, Sanchit; Mehta, Shubham; Sarangdhar, Nikhil; Ray, Animesh; Sinha, Sanjeev; Wig, Naveet
ABSTRACT: Introduction : The COVID-19 pandemic has provided global challenges to health-care facilities in ensuring the delivery of care to patients. Tremendous international collaboration has enabled the swift formulation of evidence-based guidelines that aim to clarify day-to-day issues faced by physicians and other health-care providers on the frontlines. Areas covered : In order to provide answers to the common questions and dilemmas faced by physicians and policymakers, especially those handling pulmonary manifestations of COVID-19, the authors made a list of pertinent clinical topics that were reviewed between 21st of August, 2020 to 30th of August, 2020 by the authors using online databases that included PubMed, EBSCO, and the Cochrane Library. Literature was reviewed and included based on relevance to the topics selected. The review was aimed to serve as a quick reference for addressing practical issues faced during patient care in the ongoing pandemic with a brief account of the management of COVID-19 patients as per international guidelines. Expert opinion : As more evidence continues to generate regarding the optimal methods of managing COVID-19 cases while caring for non-COVID patients concurrently, physicians will need to constantly reeducate themselves to keep pace with a rapidly evolving landscape of therapeutic options.